Migration of reflector orientation attributes in deep seismic profiles: evidence for decoupling of the Yilgarn Craton lower crust - A. J. Calvert; M. P. Doublier; M. P. Doublier (Solid Earth, 2019)
Interpretation of deep seismic data is challenging due to the lack of direct geological constraints from drilling and the more limited amount of data available from 2-D profiles in comparison to hydrocarbon exploration surveys. Thus other constraints that can be derived from the seismic data themselves can be of great value. Though the origin of most deep seismic reflections remains ambiguous, an association between seismic reflections and crustal strain, e.g. shear zones, underlies many interpretations. Estimates of the 3-D orientation of reflectors may help associate specific reflections, or regions of the crust, with geological structures mapped at the surface whose orientation and tectonic history are known. In the case of crooked 2-D onshore seismic lines, the orientation of reflections can be estimated when the range of azimuths in a common midpoint gather is greater than approximately 20∘, but integration of these local orientation attributes into an interpretation of migrated seismic data requires that they also be migrated. Here we present a simple approach to the 2-D migration of these orientation attributes that utilizes the apparent dip in reflections on the unmigrated stack and maps reflector strike, for example, to a short linear segment depending on its original position and a migration velocity. This interpretation approach has been applied to a seismic line shot across the Younami Terrane of the Australian Yilgarn Craton and indicates that the lower crust behaved differently from the overlying middle crust as the newly assembled crust collapsed during the Late Archean. Some structures related to approximately east-directed shortening are preserved in the middle crust, but the lower crust is characterized by reflectors that suggest N-NNE-oriented ductile flow. Deployment of off-line receivers during seismic acquisition allows the recording of a larger range of source-receiver azimuths and should produce more reliable future estimates of these reflector attributes.